Geospatial intelligence workforce. (5th February 2013) - Showstack, Randy
Abstract : A report on the future U.S. workforce for geospatial intelligence, requested by the U.S. National Geospatial‐Intelligence Agency (NGA), found that the agency—which hires about 300 scientists and analysts annually—is probably finding sufficient experts to fill the needs in all of its core areas, with the possible exception of geographic information systems (GIS) and remote sensing. The report by the U.S. National Research Council, released on 25 January, noted that competition for GIS applications analysts is strong. While there appear to be enough cartographers, photogrammetrists, and geodesists to meet NGA's current needs in those core areas, the report cautioned that future shortages in these areas seem likely because of a relatively small number of graduates.